Classification of longitudinal strain curves measured by speckle-tracking echocardiography in normal and pathological myocardial segments - Mirea Oana; Berceanu Mihaela; Soldea Sorina; Donoiu Ionuț; Raicea Victor (Sciendo, 2023)
Two-dimensional speckle-tracking echocardiography (2D-STE) provides a quantitative tool to evaluate LV function at the regional level. The purpose of this study was to classify the types of regional longitudinal strain curves (LSC). Moreover, we propose a novel longitudinal strain curve index (LSCI) which we compared to the wall motion score index (WMSI).